2022
DOI: 10.1038/s41598-022-09950-y
|View full text |Cite
|
Sign up to set email alerts
|

Artificial shelters provide suitable thermal habitat for a cold-blooded animal

Abstract: Human activities such as urbanization often has negative affects wildlife. However, urbanization can also be beneficial to some animals by providing suitable microhabitats. To test the impact of urbanization on cold-blooded animals, we first conducted a snake survey at a national nature reserve (Xianghai natural reserve) and an adjacent tourist bird park (Red-crowned Crane Park). We show high presence of Elaphe dione in the tourist park even with high human activities and predator population (the endangered, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…2D; Table 5). Supporting our finding, previous studies also showed that artificial structures, such as metal and riprap-covered structures, are widely utilized by lizard and snake species in urban habitats for basking and hiding (Herbert et al 2023;Watchorn et al 2023;Yu et al 2022). For example, the density of lagartixas (Tropidurus hispidus) is elevated in urbanized areas and the primary predictor of abundance was man-made structures which provide shelter (de Andrade 2020).…”
Section: Discussionsupporting
confidence: 86%
“…2D; Table 5). Supporting our finding, previous studies also showed that artificial structures, such as metal and riprap-covered structures, are widely utilized by lizard and snake species in urban habitats for basking and hiding (Herbert et al 2023;Watchorn et al 2023;Yu et al 2022). For example, the density of lagartixas (Tropidurus hispidus) is elevated in urbanized areas and the primary predictor of abundance was man-made structures which provide shelter (de Andrade 2020).…”
Section: Discussionsupporting
confidence: 86%
“…Some species may respond to fluctuations in resource abundance by, if possible, switching to other food sources (Le Bot et al 2019; Steinmetz et al 2021), reducing energetic costs by lowering body heat (Schmidt et al 2020), or entering hibernation or torpor (Boyles et al 2020; Mohr et al 2020; Fjelldal et al 2021). However, movement represents one of the most readily available behaviors that species can adjust, whether this be by modifying their home range (Lucherini and Lovari 1996; Relyea et al 2000; Arechavala-Lopez et al 2019; Hirt et al 2021; Bista et al 2022; Bradsworth et al 2022; Yu et al 2022), migrating (Middleton et al 2018; Geremia et al 2019), moving nomadically (Nandintsetseg et al 2019; Teitelbaum and Mueller 2019), or dispersing (framework: Southwood 1977; amphibians: Cayuela et al 2020; Wheat et al 2017; birds: Pretorius et al 2020; mammals: Singh et al 2012).…”
Section: Introductionmentioning
confidence: 99%